Man op brancard bij de EHBO. Uit arch. W. Hulst, nr. 31-34. Zie ook contact-afdrukken BG A28/459-484 - Meerendonk, Ben van,
Man op brancard bij de EHBO. Uit arch. W. Hulst, nr. 31-34. Zie ook contact-afdrukken BG A28/459-484.